2022
DOI: 10.1172/jci150807
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cell manufacturing from naive/stem memory T lymphocytes enhances antitumor responses while curtailing cytokine release syndrome

Abstract: Chimeric antigen receptor (CAR) T cell expansion and persistence represent key factors to achieve complete responses and prevent relapses. These features are typical of early memory T cells, which can be highly enriched through optimized manufacturing protocols. Here, we investigated the efficacy and safety profiles of CAR T cell products generated from preselected naive/stem memory T cells (T N/SCM ), as compared with unselected T cells (T BULK ). Notwithstanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 61 publications
5
70
0
Order By: Relevance
“…We found that CD4/CD8 ratio at apheresis showed a positive correlation with increased lymphocyte count at day 7 especially in the CD3 LOW group (data not shown). Furthermore, previous studies demonstrated that CAR T cell products generated from naïve/stem memory T cells, as compared with unselected T cells, shows superior antitumor activity and increase expansion rates 26 , 27 . However, because it is difficult to evaluate theses phenotypes in the clinical setting, we used lymphocyte counts in peripheral blood as a simple biomarker reflecting CAR-T cell proliferation 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that CD4/CD8 ratio at apheresis showed a positive correlation with increased lymphocyte count at day 7 especially in the CD3 LOW group (data not shown). Furthermore, previous studies demonstrated that CAR T cell products generated from naïve/stem memory T cells, as compared with unselected T cells, shows superior antitumor activity and increase expansion rates 26 , 27 . However, because it is difficult to evaluate theses phenotypes in the clinical setting, we used lymphocyte counts in peripheral blood as a simple biomarker reflecting CAR-T cell proliferation 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 138 Similarly, CAR-T cells generated from pre-selected naive and stem cell memory T cells demonstrated superior and sustained anti-leukemia activity in a humanized mouse model compared with bulk CAR-T cells. 139 CAR-T SCM cells can be reliably generated at clinical scale and were tested in a clinical trial ( NCT01087294 ).…”
Section: Car-t Cell Biology and Animal Modelsmentioning
confidence: 99%
“…Both the T-cell phenotype and T-cell subset in the starting material and final product were shown to influence the therapeutic efficacy of CAR-T cells. For instance, the application of defined ratios of T-cell subsets or manufacturing from naïve/stem memory T cells was shown to enhance anti-tumor reactivity and CAR-T persistence [ 12 , 30 , 31 ]. Hence, a better understanding of the synergistic effects of different T-cell subsets within the CAR-T product will help to improve the therapeutic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a better understanding of the synergistic effects of different T-cell subsets within the CAR-T product will help to improve the therapeutic efficacy. To do so, state-of-the-art methods require the isolation of subpopulations, separate genetic modification, and the subsequent mixing of the cell products [ 12 , 30 , 31 , 32 ]. In contrast, targeted LVs can be used to transduce defined T-cell subsets within mixed populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation